VD_FINDINFO AP / 2010 / 219 vom 25. Januar 2010 - VD Tribunal cantonal (2010)
APPEL EN CAUSE, PREUVE FACILITÉE, PRÉSENTATIONPRODUCTION, TITREDOCUMENT | 456a al. 1 CPC, 83 al. 1 let. a CPC, 83 al. 1 let. c CPC, 83 CPC